2016
DOI: 10.1007/s10461-015-1280-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Pilot Church-Based Intervention to Reduce HIV Stigma and Promote HIV Testing Among African Americans and Latinos

Abstract: HIV-related stigma and mistrust contribute to HIV disparities. Addressing stigma with faith partners may be effective, but few church-based stigma reduction interventions have been tested. We implemented a pilot intervention with 3 Latino and 2 African American churches (4 in matched pairs) in high HIV prevalence areas of Los Angeles County to reduce HIV stigma and mistrust and increase HIV testing. The intervention included HIV education and peer leader workshops, pastor-delivered sermons on HIV with imagined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 59 publications
0
50
0
Order By: Relevance
“…Attendance. Five studies examined HIV/STI in association with service attendance [49,[65][66][67][68]. Two studies were mixed methods and three were quantitative.…”
Section: Plos Onementioning
confidence: 99%
“…Attendance. Five studies examined HIV/STI in association with service attendance [49,[65][66][67][68]. Two studies were mixed methods and three were quantitative.…”
Section: Plos Onementioning
confidence: 99%
“…These interventions are grounded in behavior change theory and focus on creating space for contact between those perpetrating stigma and the stigmatized (contact strategies) ( 24 28 ), fostering empathy ( 29 32 ) and building the knowledge and skills necessary to change stigmatizing behavior ( 27 , 33 – 38 ). This evidence, coupled with years of intervention efforts, has established basic principles for stigma-reduction programming, which can be designed to operate on what are often referred to as the immediately actionable drivers of stigma ( 11 , 19 , 21 , 23 , 35 – 40 ). Those basic principles focus on contact strategies ( 24 28 ), empathy creation ( 29 32 ) and building efficacy by increasing knowledge and skills ( 27 , 33 – 38 ) for reducing stigma by: (1) increasing awareness and understanding of the concrete forms stigma takes, as health workers (or people) are often unaware that they are stigmatizing; (2) addressing the specific fears surrounding HIV transmission that drive care or treatment avoidance behaviors; and (3) working on the negative attitudes that lead to blaming and shaming by health staff who judge people living with HIV to be engaging in socially “unacceptable” behaviors or belonging to groups that are considered “lesser or other” than mainstream society.…”
Section: Introductionmentioning
confidence: 99%
“…Results from our pilot study found that, at the church level, the intervention reduced HIV stigma and HIV mistrust among the Latino churches and increased HIV testing across the African American and Latino churches. 24 Specifically, the Latino Catholic intervention church experienced a decrease between baseline and follow-up in both HIV stigma and HIV mistrust (effect size change=−0.16; 95% confidence interval [CI] −0.25 to −0.06 for HIV stigma; −0.15 for HIV mistrust; 95% CI −0.24 to −0.05). Similarly, the Latino Pentecostal intervention church experienced a significant decrease in both outcomes between baseline and follow-up (effect size change=−0.38 for HIV stigma; 95% CI −0.71 to −0.05; −0.56 for HIV mistrust; 95% CI −0.86 to −0.27).…”
Section: Introductionmentioning
confidence: 99%